Ecological footprint assessment of central java province: An input-output approach - Irawan Evi (BIO Web of Conferences)
The ecological footprint provides a vital measure of how human activities impact natural resources and the environment, highlighting the balance—or imbalance—between consumption and the Earth's capacity to regenerate resources. Understanding these dynamics is crucial for sustainable development, especially in regions facing resource constraints. This study assesses the ecological footprint of Central Java Province using an input-output approach to provide a comprehensive understanding of resource use and environmental impact across key sectors, including agriculture, forestry, fisheries, and built-up areas. By employing the 2016 input-output table and sector-specific land use data, this analysis calculates the direct and indirect land demands associated with final consumption and economic activities. The findings reveal that agriculture and fisheries exhibit the highest ecological footprints per capita, emphasizing their significant demand on land and water resources. The built-up sector, while more efficient in land use, contributes heavily to Central Java’s export economy, indicating its vital economic role. Results also highlight Central Java’s reliance on imported resources, particularly in forestry, to supplement local production, revealing the interconnectedness of regional and global resource flows. The study underscores the importance of adopting sustainable practices in high-impact sectors, such as agriculture, to reduce ecological strain and achieve a balanced resource footprint. This ecological footprint assessment offers insights into sector-specific sustainability challenges and guides policy recommendations for sustainable resource management in Central Java.